2008
DOI: 10.3748/wjg.14.5893
|View full text |Cite
|
Sign up to set email alerts
|

Effect of b value on monitoring therapeutic response by diffusion-weighted imaging

Abstract: AIM:To explore the diffusion gradient b-factor that optimizes both apparent diffusion coefficient (ADC) measurement and contrast-to-noise (CNR) fo r a s s e s s i n g t u m o r re s p o n s e t o t ra n s a r t e r i a l chemoembolization (TACE) in a rabbit model. METHODS: Twelve New Zealand white rabbits bearing VX2 tumors in the liver were treated with TACE. Diffusion-weighted imaging (DWI) with various b values was performed using the same protocol before and 3 d after treatment with TACE. ADC values and CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…For tumours that exhibit considerable heterogeneity (e.g. mixed solid, necrotic and cystic), some authors have suggested using multiple ROIs to evaluate sub-regions within these tumours [ 44 ] . However, there may be subjectivity and bias in such ROI placements.…”
Section: Diffusion-weighted Mr Imaging (Dwi) For Assessing Tumour Resmentioning
confidence: 99%
“…For tumours that exhibit considerable heterogeneity (e.g. mixed solid, necrotic and cystic), some authors have suggested using multiple ROIs to evaluate sub-regions within these tumours [ 44 ] . However, there may be subjectivity and bias in such ROI placements.…”
Section: Diffusion-weighted Mr Imaging (Dwi) For Assessing Tumour Resmentioning
confidence: 99%
“…It enables quantitative analyses by measuring the standard apparent diffusion coefficient (ADC) value. Thus, this technique can be used to evaluate TACE response for HCC [9]- [14]. But conventional DWI with a mono-exponential model could not separate perfusion and true diffusion-related effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not applicable for patients with contraindications to MR imaging. Respiratory motion is a major issue in hepatic perfusion imaging ( 31 32 ). Second, in the present study, the RECIST (Version 1.1) criteria based on tumor size, but not the mRECIST based on tumor enhancement, were used for evaluating therapeutic response to TACLI.…”
Section: Discussionmentioning
confidence: 99%